Properties of surface plasmon polaritons on lossy materials: lifetimes, periods and excitation conditions. (20th October 2016) - Derrien, Thibault J-Y; Krüger, Jörg; Bonse, Jörn
Abstract: The possibility to excite surface plasmon polaritons (SPPs) at the interface between two media depends on the optical properties of both media and geometrical aspects. Specific conditions allowing the coupling of light with a plasmon-active interface must be satisfied. Plasmonic effects are well described in noble metals where the imaginary part of the dielectric permittivity is often neglected ('perfect medium approximation (PMA)'). However, some systems exist for which such approximation cannot be applied, hence requiring a refinement of the common SPP theory. In this context, several properties of SPPs such as excitation conditions, period of the electromagnetic field modulation and SPP lifetime then may strongly deviate from that of the PMA. In this paper, calculations taking into account the imaginary part of the dielectric permittivities are presented. The model identifies analytical terms which should not be neglected in the mathematical description of SPPs on lossy materials. These calculations are applied to numerous material combinations resulting in a prediction of the corresponding SPP features. A list of plasmon-active interfaces is provided along with a quantification of the above mentioned SPP properties in the regime where the PMA is not applicable.